Serbisyo publi(ko) an investigative study on the necessity of an anti-signage of public works law - Riego, Norman Lee Benjamin De Leon 1990-; Mangunay, Kristine Felisse (2012)
"This study is an investigation on the prevailing practice of politicians to plaster their names and/or faces in public works such as establishments, vehicles, service programs and campaigns. This study then juxtaposed the issue with the push for a law to curb such practice, more commonly known as the "Anti-Signage of Public Works Law." It delved on the necessity for such law to be pursued. Through archival and contemporary research, this study analyzed and synthesized the bills concerned. It also gathered the current costs and conditions of such practice to allow a more concrete grasp of the issues as a whole. Through firsthand interviews, this study weighed the motivations and implications of both legislators and politicians. Their perspectives were compared and contrasted to come up with a study of the ethical dimension of the issues as a whole."
Vita.
Undergraduate thesis (A.B. Journalism)--University of the Philippines.
Keywords: Anti-Sinage of Public Works Law; Public works -- Law and legislation -- Philippines